Thorny brinjal blooming in Thar desert - Singh, P P; Verma, A K (Indian Horticulture, 2019)
Brinjal is one of the most important fruit vegetables. As it originated in India, wide range of variability is found in fruit size, colour and shape. The optimum temperature for normal growth and development of plant and fruits is 21-30oC or below, but high temperature range in hot arid agroclimate makes its cultivation difficult as it affects fruit setting. To mitigate this problem, a line of brinjal, viz. AHTB having thorns on its leaves and fruit calyx was identified which has the potential to set fruits at high temperature during summer and give high yield under hot arid conditions. Besides, having high yield potential under high temperature conditions, it is also fairly tolerant to major pest and diseases.